The nature of the atonement - Campbell, John McLeod, 1800-1872 (Edinburgh, Scotland Handsel, 1996)
Includes bibliographical references and indexes.
Originally published in 1856 by MacMillan as : The nature of the atonement and its relation to remission of sins and eternal life
Keywords: Atonement; Forgiveness of sin